Experimental studies on industrial scale metal hydride based hydrogen storage system with embedded cooling tubes. (21st May 2019) - Kumar, Alok; Raju, Nithin N.; Muthukumar, P.; Selvan, P. Vivek
Abstract: The present article reports the activation and testing of large scale metal hydride based hydrogen storage system (MHHSS) for industrial application. The metal hydride reactor is fabricated using SS316 material with 99 embedded cooling tube and filled with 40 kg of LaNi4.7 Al0.3 . The activation was carried out by successive absorption and desorption processes. In the third absorption cycle, MHHSS had absorbed 552.356 g of hydrogen to reach a maximum storage capacity of 1.4 wt% at 40 bar pressure and 30 °C temperature. The testing of MHHSS was carried out by varying H2 supply pressure, absorption and desorption temperatures and heat transfer fluid (HTF) flow rate. It was observed that the supply pressure has significant effect on absorption rate, and the optimum supply pressure was observed in the range of 10–15 bar. Similarly, during the desorption cycle, optimum desorption temperature was found in the range of 80–90 °C. The optimum flow velocity for HTF was observed in the range of 20–30 lpm. Graphical abstract: Image 1 Highlights: Industrial scale MH based hydrogen storage (MHHS) system has been fabricated. Parametric studies on MHHS system have been carried out by varying key parameters. Variation in MH bed temperature during absorption/desorption process is presented. Optimum working conditions for H2 absorption/desorption has been found out.